2012
DOI: 10.4236/fns.2012.36111
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Pasting Properties of Oat <i>β</i>-Glucan Hydrocolloids

Abstract: Four oat β-glucan enriched hydrocolloids (Nutrim10, C-Trim20, C-Trim30, C-Trim50), oat bran concentrate (OBC), and β-Glucan95 were investigated for antioxidant and pasting properties. C-Trim30 had the highest soluble phenolic content, followed by C-Trim20. The trend of antioxidant activity was similar with that of phenolic contents. The phenolic content of the extracts increased with increasing temperatures. The highest content of soluble phenolic compounds was found at temperatures up to 100˚C for most sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…AVAs helps in preventing free radicals from damaging LDL cholesterol (Singh et al 2013) and AVAs-enriched extract of oats combined with vitamin C synergistically inhibits LDL oxidation in vitro (Meydani 2009). Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
“…AVAs helps in preventing free radicals from damaging LDL cholesterol (Singh et al 2013) and AVAs-enriched extract of oats combined with vitamin C synergistically inhibits LDL oxidation in vitro (Meydani 2009). Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%
“…Oat, a type of whole grain, has gained increasing popularity, as it contains components such as bran and β-glucan, which are sources of dietary fiber for healthy food formulation ( 4 ). Moreover, oat is a commonly used grain and contains many phytochemicals that exhibit antioxidant activity, such as tocols, flavonoids, phytic acid, and phenolic acids ( 5 , 6 ). β-Glucan together with other phytochemicals are concentrated in the bran layer of oat grain that provide functional properties to the bran ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oat is characterized by a high content of lipids, 2-3 times more than other cereals and a high protein content that can be of great exogenous source of amino acids (Butt et al, 2008) Likewise, fibers from oat can bring important benefits to the health of the digestive tract, due to the contribution of the increase of faecal mass. In addition to β-glucans benefits, products derived from oat had a significant content of phenolic compounds and other antioxidants, (Madhujith and Shahidi 2007;Inglett and Chen 2012).…”
Section: Introductionmentioning
confidence: 99%